Psycho-cognitive effects of the expectancy of score-based feedback in an activity involving artistic emotional expression - Dağ, Özge. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
Feedback-based control is being used extensively in modern technology with great success to make systems behave in a desired manner. Also for human performers, receiving feedback about their performances provides opportunity to learn from their errors and deficiencies. However, with the wide-spread usage of performance improvement policies with score-based feedback, some adverse psycho-social effects started being reported. The purpose of this thesis is to design and implement an experiment for investigating how the “type” of performance feedback, i.e. whether the information is represented in a qualitative or quantitative manner, affects the human performer. For this study, an original task has been developed that involves artistic expression of emotions. The psychological correlates of the expected effects have been sought for via questionnaire-based methods, while their neural correlates have been investigated via seed-based functional connectivity analysis of fMRI recordings.
Keywords: Cognitive science.; Emotions.